GEOCHEMICAL FEATURES OF HOST ROCKS OF THE POROKHOVSKOE TUNGSTEN DEPOSIT (SOUTH URALS) AND THEIR ROLE IN CONCENTRATION OF ORE MATTER - K.P. Maltseva; E.V. Belogub; K.A. Novoselov; D.A. Rogov; R.R. Irmakov (Минералогия)
The article contains the results of statistical processing of geochemical data for rocks of the Porokhovskoe tungsten deposit (South Urals) obtained during systematic geological exploration. Statistical samplings were formed for various types of host rocks: andesites and their tuffs, shales, metasomatites (including sericite-quartz, epidote and chlorite-bearing) and skarns. It is established that all rocks of the Porokhovskoe deposit are characterized by increased contents of W and Mo and, to a lesser extent, Be, Cu, Li, and Zn and by stable groups of correlated elements, both associated with greisenization process and those inherited from the protolith. No zoning is revealed in the distribution of elements in relation to the Yugo-Konevsky leucogranitic pluton, which is considered the ore-generating for the deposit. No correlation between W and Mo was identified in all types of host rocks. A number of statistical methods is proposed for the identification of promising areas with unclear W-Mo mineralization in rocks.